2022
DOI: 10.1186/s13018-022-02932-w
|View full text |Cite
|
Sign up to set email alerts
|

Utility of a novel integrated deep convolutional neural network for the segmentation of hip joint from computed tomography images in the preoperative planning of total hip arthroplasty

Abstract: Purpose Preoperative three-dimensional planning is important for total hip arthroplasty. To simulate the placement of joint implants on computed tomography (CT), pelvis and femur must be segmented. Accurate and rapid segmentation of the hip joint is challenging. This study aimed to develop a novel deep learning network, named Changmugu Net (CMG Net), which could achieve accurate segmentation of the femur and pelvis. Methods The overall deep neural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Such solutions have been shown to be effective used in trauma patients and may be helpful in pre-surgical planning of RHA [44] Another method is the use of neural network (NN) and artificial intelligence (AI) in the process of bone tissue segmentation [45]. Wu et al [46] showed that the use of new neural networks (e.g., CNN-CMG Net) increases the accuracy of bone tissue segmentation while reducing the time required to create 3D models of such anatomical structures, which clearly indicates a potential research direction to optimize the presurgical planning process. However, it should be emphasized that these promising results focused on healthy bone tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Such solutions have been shown to be effective used in trauma patients and may be helpful in pre-surgical planning of RHA [44] Another method is the use of neural network (NN) and artificial intelligence (AI) in the process of bone tissue segmentation [45]. Wu et al [46] showed that the use of new neural networks (e.g., CNN-CMG Net) increases the accuracy of bone tissue segmentation while reducing the time required to create 3D models of such anatomical structures, which clearly indicates a potential research direction to optimize the presurgical planning process. However, it should be emphasized that these promising results focused on healthy bone tissue.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, quantitative analysis of CT data, such as artificial intelligence–assisted preoperative planning (AI‐hip, Longwood Valley MedTech, Beijing, China), 7 is an efficient way to visualize the bone defect located at the superolateral aspect of the acetabulum, and to predict the precise data of uncoverage when the acetabular cup is placed at 40° of inclination and 15° of anteversion at the level of true acetabulum. The intelligent image segmentation system of AI‐assisted preoperative planning (AI‐HIP software, Longwood Valley MedTech, Beijing, China) is based on convolutional neural networks and deep learning algorithms, and was constructed on the basis of over 1.2 million CT images from 3000 patients.…”
Section: Methodsmentioning
confidence: 99%
“…The comprehensive workflow is integrated into the AI‐HIP software. The accuracy of the AI‐HIP has been validated through several clinical studies 7 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work, we chose the task of segmenting bones from computed tomography (CT) images for total hip arthroplasty (THA) planning. Most works that relied on deep learning to segment (some) bones of the hip from CT in the context of THA [ 15 , 16 ] used basic geometric augmentations such as rotation, translation, scaling, cropping, and left–right flipping. This was also observed with other studies that did not focus on THA but also segmented bones of the hip joint from CT [ 17 ] and sometimes included simple intensity augmentations such as intensity scaling [ 18 ].…”
Section: Introductionmentioning
confidence: 99%